Study on Palmaris Longus Muscle Tendon Agenesis Among First Year Filipino Medical Students - Lamichhane, Pujan Sharma; Sharma, K; Lamichhane, N (Journal of Gandaki Medical College-Nepal, 2017)
Introduction: In the recent years palmaris longus muscle tendon (PLMT) has become an extensively and intensively studied muscle all over the world. The main reason for this is the importance of PLMT which was recognized with development of plastic and reconstructive surgery. The possibilities of PLMT use has become bigger and bigger each day Objectives: The study aimed to evaluate the incidence of agenesis of palmaris longus muscle tendon among first year Filipino medical students at OLFU. Methods: This study was conducted at the Our Lady of Fatima University Medical Centre, Valenzuela City, Philippines. A semi-structured proforma was used to record the relevant data for the study. The Thompson’s test was used for assessing palmaris longus muscle tendon. After taking consent total of 503 first year Filipino medical students were involved. Results: Out of total 503 subjects, 170 (33.80%) were males and 333 (66.20%) were females. Percentage of frequency of agenesis of palmaris longus muscle tendon in both genders was 17.05%. There was no significant gender and laterality difference in the incidence of the agenesis of palmaris longus muscle tendon. That means there are equal chances of palmaris longus muscle tendon agenesis in both gender and the laterality. Conclusions: There was no significant gender and laterality difference in the incidence of the agenesis of PLMT. This means that there are equal chances of PLMT agenesis in both gender and the laterality. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 17-20